Pengaruh Musik Klasik Terhadap Tekanan Darah Pada Pasien Hipertensi di Klinik Ambalat SESKO TNI Bandung - Riski Mulia Agustina; Sri Mulyeni (Journal of Educational Innovation and Public Health, 2024)
Hypertension or high blood pressure is a disease that is often suffered by many people, hypertension itself sometimes has symptoms that the sufferer does not know about. A condition that causes about half of all deaths from stroke and heart disease. The aim of this study aims to determine the effect of classical music therapy on changes in blood pressure in hypertensive patients at the Ambalat SESKO TNI Bandung Clinic. This research uses a quantitative questionnaire method with a pre-post test research design (Quasy experiment), the data analysis used is the Wicoxon test. The respondents were 25 TNI members at the Ambalat SESKO TNI Bandung Clinic. The instruments in this study used a sphygmomanometer and classical music.